Five-year outcomes of trabeculo-canalectomy for Chinese PACG patients: a retrospective study - Zhan Xie; Tianhao Xiao; Junlong Huang; Mulong Du; Ping Zhang; Ying-Ting Zhu; Ping Xie; Hong Sun (BMC Ophthalmology)
Abstract Background To evaluate the 5-year outcomes of trabeculo-canalectomy in the treatment of primary angle-closure glaucoma (PACG) among Chinese patients. Methods A retrospective study was designed, involving 46 PACG patients (50 eyes) treated with trabeculo-canalectomy at the First Affiliated Hospital of Nanjing Medical University from January 2016 to December 2018. The patients were followed up at 1 week, 1 month, 3 months, 6 months, 12 months, 1 year, 2 years and 5 years. Surgical success was defined as intraocular pressure (IOP) ≤ 21 mmHg (1 mmHg = 0.133 kPa) under glaucoma medication (qualified success) and without any glaucoma medication (absolute success). Main outcomes were measured according to IOP, number of medication regimens, surgical success rate, complications, and filtering bleb status. Results A total of 46 PACG patients (50 eyes) were finally included for statistical analysis, with a mean age of 56.68 ± 6.75 years (range, 41–69 years). The mean preoperative IOP was 30.72 ± 10.26 mmHg with a median number of medication regimens of 2 (range, 0 to 4). Compared to those before the operation, the mean IOP decreased to 12.15 ± 3.11, 14.33 ± 4.10, 15.68 ± 4.24, 16.45 ± 4.14, 16.95 ± 3.51, 17.67 ± 3.15 and 17.04 ± 3.78 mmHg at 1 week, 1 month, 3 months, 6 months, 12 months, 1 year, 2 years and 5 years, respectively. The median (range) numbers of medication regimens were 0 (0 ~ 1), 0 (0 ~ 2), 0 (0 ~ 2), 0 (0 ~ 2), 0 (0 ~ 2), 0 (0 ~ 3), 0 (0 ~ 3), 0 (0 ~ 3) at the eight time points, respectively. The mean postoperative IOP and the number of medication regimens at each time point were significantly lower than those before operation (all P < 0.01). The 5-year total success rate was 89%, and the absolute success rate was 78%. Shallow anterior chamber (10%) and hyphema (12%) were the most common complications early after surgery. At 3 months, anterior segment slit-lamp photography and ultrasound biomicroscopy showed no obvious filtering blebs in 50 eyes (100%). IOP increased transiently in 6 eyes (12%) within 1 month after surgery. Conclusion Simple and cost-saving trabeculo-canalectomy provides favorable 5-year outcomes in the treatment of medically uncontrolled PACG, as shown by more effective IOP control, more obvious drug reduction, as well as fewer post-operative interventions compared to trabeculectomy.